Long-term safety and effectiveness of Rezafungin treatment in candidemia and invasive candidiasis: results from an early access program in Italy and Germany - Trapani, Filippo; Viceconte, Giulio; Morena, Valentina; Tiseo, Giusy; Mori, Giovanni; Kölking, Britta; Khatamzas, Elham (Open Forum Infectious Diseases, 2025)
Outcomes are reported for 6 adults receiving rezafungin for chronic, hard-to-treat, invasive candidiasis (including Candida parapsilosis) during an early access program. Rezafungin was well tolerated and administered via once-weekly outpatient intravenous infusion for up to 39 weeks during the program, enabling hospital discharge and replacing daily antifungal infusions.
Veröffentlicht: 19. März 2025
Gesehen am 19.08.2025